Biofortification of Cicer arietinum to enhance nutrient-rich diets in semi-arid regions - Jyoti Rani; Deepak Beniwal; Sahil Singh Dhull; Vibhuti Gulia; Poonam Sangwan; Gholamreza Abdi (Discover Sustainability)
Abstract Micronutrient malnutrition, notably iron (Fe) and zinc (Zn) deficiencies, poses a significant global health challenge, particularly among populations dependent on cereal-based diets in semi-arid regions. Chickpea (Cicer arietinum L.) is a nutrient-rich legume and staple food in many developing countries, making it a key target for biofortification efforts aimed at mitigating these deficiencies. This review consolidates recent progress in agronomic and genetic strategies for enhancing chickpea micronutrient density while addressing challenges related to bioavailability. Agronomic interventions, including micronutrient fertilization through soil and foliar applications, are assessed alongside traditional breeding methods and innovative genetic engineering techniques such as genome editing, to sustainably boost Fe and Zn levels of chickpea. Additionally, this review situates chickpea biofortification within the larger context of global malnutrition, underlining its importance in semi-arid agroecological areas where soil nutrient depletion and climate variability exacerbate dietary deficiencies. Limitations such as potential yield trade-offs, socioeconomic barriers, and environmental issues are examined. Furthermore, the paper emphasizes the need for integrating biofortification with climate-resilient agricultural practices to ensure sustainability in semi-arid regions, where water scarcity and soil degradation further limit nutritional outputs. Ultimately, the review highlights effective integrated approaches and policy strategies that can promote the development and dissemination of nutrient-enriched chickpea varieties, thereby enhancing long-term nutritional security in resource-limited regions. Such an approach aligns with global goals for zero hunger and better health outcomes, making biofortified chickpeas a vital component in combating ‘hidden hunger’ in marginalized populations.